Development is Anti-Democratic - Lummis, C. Douglas (Kasarinlan: Philippine Journal of Third World Studies; Vol 6 No 3 (1991), 2009)
Economic development is anti-democratic in several ways. It is anti-democratic in that it requires kinds, conditions, and amounts of labor that people would never choose--and, historically, never have chose--in a state of freedom. Economic development is also anti-democratic because it promotes social inequality. Economic development is anti-democratic for it is a process of establishing and strengthening an undemocratic form of rule over a central aspect of people's lives--their work--and also in that it generates inequality in wealth and power. In addition, it is anti-democratic because people's attention is turned away from political goals and struggles, and are then replaced with "economic" ones. Economic development is anti-democratic in that it is the expansion of a sphere of life from which democracy is to be excluded in principle.